Andrea Giordano, Michele Russo, Roberta Spallone (Eds), Representation Challenges. Augmented Reality and Artificial Intelligence in Cultural Heritage and Innovative Design Domain, FrancoAngeli, Milano 2021 (diségno, 2021)
About 20 years ago, eidomatics has fully entered our professional sphere. Since then, we represent and measure with computer the reality that surrounds us, we model ideas of the past, present and future, we virtually travel in space and time. Therefore, we have been using the technologies that the market offers us for about 20 years, referring to them with the adjective ‘new’. [read more]